Genetic diversity of urogenital Chlamydia trachomatis before and after mass drug administration for trachoma. Issue 2 (28th February 2020) - Baltas, Ioannis; Pickering, Harry; Beale, Mathew; Holland, Martin; Versteeg, Aalbartus; Mabey, David; Roberts, Chrissy H.; Kako, Henry; Solomon, Anthony; Thompson, Nick; Marks, Michael; Butcher, Robert
Abstract : Background: The WHO recommends treatment of trachoma with community-wide mass drug administration (MDA) with a single dose of azithromycin as part of the SAFE strategy (surgery, antibiotics, facial cleanliness and environmental improvement). In the Solomon Islands, this programme had demonstrable collateral benefit by reducing the prevalence of urogenital Chlamydia trachomatis(Ct) infections. We evaluated the impact of this treatment on population genetics of urogenital Ct. Methods Two vaginal swabs were collected from consecutive women attending antenatal clinics during cross-sectional surveys before and after MDA. For every swab positive for Ctinfection, DNA was extracted from the second swab, enriched and sequenced using paired-end sequencing. Whole-genome sequences were aligned against selected references. Diversity was assessed using genome-wide pairwise diversity and a high-resolution multi-locus sequence typing (hr-MLST-6) scheme. ARIBA software was used to test for evidence of antimicrobial resistance to macrolides. Results: Whole-genome sequence data was obtained from 23/49 (47%) pre-MDA and 32/41 (78%) post-MDA Ct-positive samples. Most strains were serotype E and F, and tissue tropism genes were consistent with their urogenital nature. Genetic diversity of Ctwas lower by both pairwise and hr-MLST-6 diversity metrics in the post-MDA sample than the pre-MDA sample. There was no evidence of mutations known to confer resistance to macrolides in any of the samples collected. Conclusions Reduced diversity after MDA may represent selection pressure from mass antibiotic delivery. The absence of antimicrobial resistance is encouraging. The collateral impact (both positive and negative) of large-scale preventative chemotherapy programmes should be considered when deciding whether should be implemented.